Wastewater Treatment by Continuous Stirred Tank Reactor (CSTR) - Go Bee, Chew (2013)
The adsorption has been used for the industrial wastewater treatment, the batch and continuous studies were done. The aim of this study is to develop a new adsorption reactor to continuous removal of the contaminants which is the Continuous Stirred Tank Reactor (CSTR). The adsorbent used was the powdered activated carbon. By the batch studies, the equilibrium and kinetic parameters have been evaluated. Langmuir isotherm was been represented for equilibrium data and the ‘unified approach model’ which recently developed was been used to represent the kinetic data. The CSTR performance was studied and found that the CSTR operates as an ideal CSTR. Effect of initial concentration, contact time and adsorbent dosing rate on the dye removal efficiency in CSTR unit has been investigated.